2016
DOI: 10.1016/j.diamond.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

CVD diamond growth from nanodiamond seeds buried under a thin chromium layer

Abstract:  Carbon diffusion into the Cr layer during the early CVD diamond growth stages  Carburization and salicidation of the Cr layer in the high-temperature, H-rich plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The top surface microstructure (Figure 4a) is also nanocrystalline in nature, with rounded micron sized granular features present throughout the matrix. There are cracks present in the microstructure, as also found previously by researchers with respect to a sputtered Cr layer [52]. Some of the grains are loosely bound to the bottom layer.…”
Section: Ti Pvd Sputtering and H 2 Plasma-etching Of Ti-mcd Composite...supporting
confidence: 80%
See 1 more Smart Citation
“…The top surface microstructure (Figure 4a) is also nanocrystalline in nature, with rounded micron sized granular features present throughout the matrix. There are cracks present in the microstructure, as also found previously by researchers with respect to a sputtered Cr layer [52]. Some of the grains are loosely bound to the bottom layer.…”
Section: Ti Pvd Sputtering and H 2 Plasma-etching Of Ti-mcd Composite...supporting
confidence: 80%
“…Figure 5a shows that there are exposed bottom layer diamond surfaces from place to place, which helped in the nucleation and growth of the next diamond layer. Researchers have previously reported a similar seeding method via a carbon transport phenomenon from the buried layers [52][53][54].…”
Section: Ti Pvd Sputtering and H 2 Plasma-etching Of Ti-mcd Composite...mentioning
confidence: 99%
“…O diffusion is also observed, but in a much lower level [ 27 ]. The presence of Cr at the interface region can lead to reactions with the carbon species in the growth plasma, forming chromium carbide [ 16 , 28 , 29 , 30 ], that can suppress the formation of amorphous carbon ( a - C ), inducing the formation of diamond nuclei, and at the same time provide an enhanced bonding to the LNO substrate. The Cr interlayer interacts very well with both the NCD and LNO materials, not only improving the adhesion but also suppressing the diffusion of oxygen into the NCD films, while allowing the Li to diffuse through and be efficiently incorporated into the NCD films.…”
Section: Resultsmentioning
confidence: 99%
“…The Cr-coating was deposited by a home-built DC-pulsed sputtering system using a radio frequency power of 200 W in Ar gas for 10 min. The Cr-coated LNO (Cr/LNO) substrates were then nucleated with a water-based state-of-the-art colloidal suspension of ultradispersed detonation diamond (Nano-Carbon Institute Co., Ltd., Nagano, Japan; zeta potential of (45 ± 5) mV and particle size of 6–7 nm) via drop casting and subsequent spin-drying [ 16 ]. The growth of ~90 nm thick NCD layers, designated as NCD/Cr/LNO films, was performed in a linear antenna microwave plasma enhanced chemical vapor deposition (LA CVD) system using plasma containing 10% methane in hydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…As Bareiß et al [84] and Kellerman et al [86] have shown this phase control is fundamental. A good guide to obtain such control is the work of Degutis et al [88] that verified chromium carbide layer reaction during CVD diamond growth.…”
Section: Chromium Carbidesmentioning
confidence: 99%